Preparation and property study of geopolymer composite fireproof coating with PVA fiber and manganese slag - Zhenyu Zhou; Chenxi Zeng; Hongqing Wei; Yanhuai Ding (Cleaner Materials)
Geopolymers have garnered widespread attention due to their excellent mechanical properties, durability, and fire resistance. In this paper, we have conducted the design of a geopolymer coating, incorporating a specific proportion of solid waste manganese slag and polyvinyl alcohol (PVA) fibers. The geopolymer serves to stabilize the manganese slag, while the PVA fibers enhance the mechanical properties of the coating. The results demonstrate that the composite geopolymer coating becomes dense at high temperatures, exhibiting outstanding fire-resistant characteristics. Furthermore, the coating significantly enhances the mechanical performance of wood specimens, indicating promising application prospects in the field of building material fire protection.